Plume rise and dispersion: effects of exit velocity and atmospheric stability - Cermak, Jack E., author; Meroney, Robert N., author; Petersen, Ronald L., author; Fluid Dynamics and Diffusion Laboratory, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1977)
Plume rise and dispersion was studied under stable and neutral stratification in an environmentally controlled wind tunnel. A 1:300 model of a power plant stack was constructed and positioned in the wind tunnel to assess the effect of exit velocity and temperature on plume rise and dispersion. The complete test scenario for each stability included five exit velocities (from 12.5 to 250 m/s), three exit temperatures (200, 366 and 422°K) and three stratifications (D, E and F). The exit velocity was varied by adding nozzles of different diameter to the stack top while maintaining a constant volume flow. Exit temperature variations were simulated by mixing equivalent density mixtures of helium and air. For each test case plume dispersion was assessed by traversing the plume at incremental altitudes and three downwind locations. Concentrations of the helium tracer gas were measured continuously with a Thermal Conductivity Gas Chromatograph. Plume rise was assessed using photographic techniques and by analyzing the concentration data. The results show the expected tendency for increased plume rise with increased exit velocity. More significant is the decrease in maximum centerline concentration at a given downwind distance when exit velocity increases. Curves comparing the standard plume dispersion model with the wind tunnel results are presented. Also present are the plume centerline trajectories for each case studied.
CER76-77RLP-JEC-RNM59.
Prepared under Contract to North American Weather Consultants.
June 1977.
Keywords: Wind tunnel models; Smoke plumes